Deriving strong association mining rules using a dependency criterion, the lift measure. (16th April 2009) - Bagui, Sikha; Just, Jiri; Bagui, Subhash C.
Traditional association mining rule algorithms have two major drawbacks: first, there is a need to repeatedly scan the dataset and second, they generate too many association rules. In this paper, we have presented a dependency-based association mining rule algorithm, implemented using an array list structure in JAVA, that does not require more than one scan of the full dataset and generates a lot less strong association mining rules. The additional dependency criterion used was the lift measure.